Profil Pemeriksaan Hematologi Rutin Pada Pasien HIV dan HIV dengan TB di RSUD Kota Kendari - Kolewora, Yusuf Musafir; Thamrin, Hilma Yuniar; Asrul, Muhamad; Nelini, Nelini; Rahim, Ermawati (LPPM Institut Pendidikan Nusantara Global, 2025)
HIV and TB are a combination disease that can cause death and can accelerate the development of disease between the two. HIV and TB disease affect each other in all aspects and people infected with HIV are more prone to being infected with active TB, which is around 21-34 times, compared to people who are HIV negative. Objective to find out the profile of routine hematology examinations in HIV and HIV patients with TB at Kendari City Hospital. Method The research design uses a retrospective descriptive, namely by describing and interpreting an object according to the existing data. This study was a non-experimental study because it did not control the research variables and the researchers collected data on the results of the medical records of Kendari City General Hospital patients in 2022/2023 as many as 33 samples. Results Neutrophils increased in HIV patients, Lymphocytes decreased in HIV and HIV patients with TB, and Hemoglobin decreased in HIV patients with TB. Discussion shows that neutrophil parameters increase in HIV patients due to increased inflammatory activity. Decreased lymphocyte levels in HIV and HIV patients with TB are due to decreased immune response in the body. While Hb levels decrease in HIV patients with TB due to TB disease there is an abnormality which is anemia. Anemia is characterized by decreased hemoglobin levels in the body. Conclusion Decreased lymphocyte levels in HIV patients are due to decreased immune response in the body. Meanwhile, decreased hemoglobin levels in HIV-infected patients with TB are due to TB disease having an abnormality which is anemia.